Labor Dependence, Income Diversification, Rural Credit, and Technical Efficiency of Small-Holder Coffee Farms: A Case Study of Cu M'gar District, Dak Lak Province, Vietnam - Ho, Quoc Thong (University of Economics Ho Chi Minh City, 2023)
Vietnam coffee sector plays a crucial role not only in the country’s economy but also in the global coffee market, and improving coffee production efficiency may benefit coffee producers. However, small-holder coffee farming households still encounter many difficulties regarding resources and socio-economic conditions affecting coffee production efficiency. This study examines relationships among income diversification, rural credit loan, labor dependence, and technical efficiency in coffee production through a face-to-face survey with participation of 143 coffee farming households conducted in Cu M’gar District, Dak Lak Province, Vietnam. The stochastic frontier model shows that the mean of technical efficiency scores is 0.64, and it also verifies the existence of inefficiency variation. Both Maximum Likelihood Estimate (MLE) and Feasible Generalized Least Square (FGLS) consistently indicate that a higher level of diversity in income sources negatively affects coffee production efficiency. Additionally, independence in labor resource for coffee farming may help farmers increase technical efficiency of coffee production. Credit loan has a positive and statistically significant relationship with technical efficiency of coffee production. These relationships hold especially true for smallholder coffee farms with ethnic minority household heads. The policy options of credit loan access, intensive investment in coffee production rather than diversification of coffee farmers’ income sources, and independent management strategies for labor sources are suggested as an integrated approach to improve technical efficiency in coffee production of smallholder coffee farms.